Evidence-Based Nursing Practice in Ghana - Judith A. Anaman-Torgbor PhD, MPhil, RN; Felix K. Nyande PhD, MPhil, RN; Margaret Amenuke PhD, MPH, RM, RN; Bernice Gyapong MSc, RM, RN; Dzifa Dodunoo PhD, RN; Elvis Tarkang PhD, MSc, BSc, RH (SAGE Publishing, 2022)
Introduction: The nursing profession in the 21st century requires service delivery in a highly specialized nursing environment with a high degree of professionalism and optimum patient outcome. Evidence-Based Nursing Practice (EBP) may provide a great opportunity for moving nursing care to a level that may involve clinical reasoning to meet demand in the 21st century and beyond, improve patient outcome and cost containment. Objective To investigate evidence-based nursing practice among nurses in Ghana. Methods This is a descriptive cross-sectional survey and data was collected among clinical nurses and nurse educators from both private and public institutions across Ghana. Nurses were included if they have full-time or part-time appointment; were in active service and have a valid Personal Identification Number (PIN) from the Nursing and Midwifery Council of Ghana. Results About half of the nurses disagreed or were neutral regarding formulation of answerable research questions and 40% do not critically track relevant scientific evidence. Also, more than 30% of the nurses disagreed or were neutral regarding the integration of scientific evidence into practice. Clinical nurses were about 2.1 times more likely to have difficulty determining the applicability of research findings in service delivery compared to nurse educators. Conclusion The findings suggest EBP uptake and integration is suboptimal in Ghana.